Handbook of research on emerging technologies for electrical power planning, analysis, and optimization - Shandilya, Smita, 1982-; Shandilya, Shishir; Thakur, Tripta; Nagar, Atulya; IGI eBooks; IGI Global (Hershey, Pennsylvania (701 E. Chocolate Avenue, Hershey, PA 17033, USA) : IGI Global, 2016)
"This book features emergent methods and research in the systemic and strategic planning of energy usage, highlighting theoretical perspectives and empirical research"--Provided by publisher.
Global and local clustering-based regression models to forecast power consumption in buildings / Gonzalo Vergara [and 5 others] -- Building automation systems: recent trends, design and development / Jignesh G. Bhatt -- Contemporary energy management systems and future prospects / Amir Manzoor -- Energy management in cloud computing / Ganesh Neelakanta Iyer, Pattabhi Mary Jyosthna, Suman Jonnalagadda -- Fuzzy logic based approach for power system fault section analysis / Neeti Dugaya, Smita Shandilya -- Parameter estimation of an high performance I.M. drive for sensorless operation / Monika Dixit, Smita Shandilya -- Restructuring power industry in India / Kashika Dubey Pathak -- Application of soft computing techniques in power engineering / Vivek Venkobarao -- Smart grid and cloud computing / Girish Neelakanta Iyer, Ganesh Neelakanta Iyer.
Includes bibliographical references and index.
Also available in print.
Mode of access: World Wide Web.
Description based on title screen (IGI Global, viewed 03/16/2016).
Keywords: Electric power production -- Technological innovations; Electric power consumption; Electric utilities -- Planning; Artificial neural networks; Automation systems; Electrical faults; Energy loss; Energy management; Load uncertainty; Soft computing; Electronic books